EVALUATION OF GENOTYPIC AND GENETIC VARIANCES OF QUANTITATIVE TRAITS IN PEA (PISUM SATIVUM L.) - Kosev, Valentin; Georgieva, Natalia (Emirates Journal of Food and Agriculture, 2016)
A new approach has been applied for identification of the changes in gene spectra, in accordance with the graphic model of Hayman, which allows making a comparison of varieties, presented in the graphics, as well as, a new method for interpretation of the change in location of certain varieties, with respect to given signs, at different environmental limits. In the genetic control of the characteristics of plant weight and seed weight per plant, a major role plays gene over-domination. The results obtained indicate a possibility of assessment of field peas genotypes by genetic-physiological systems in different environmental limits. No universal donor has been established between hybrids for attraction and adaptability. From selection point of view, of interest are the hybrids №11 (E.F.B.33 × Mir) with respect to green biomass (forage)and №12 (E.F.B.33 × Pleven 10), and with respect to seed №9 (Pleven 10 × E.F.B.33). Assessment of the source material, according to genetic-physiological systems, allows, with a higher degree of probability, to select an appropriate genotype, which exceeds the parental forms, in terms of productivity and ecological stability, and also to accelerate the process of creating new pea varieties.